Case report: Multi-antibody–positive myasthenia gravis concomitant myositis associated with thymoma - Huang, Chao; Dai, Xuelian; Liu, Jiacheng; Zhang, Yunting; Yin, Bianli; Liu, Chao; Ren, Xiangyang; Duan, Zhihui; Yang, Huan (Frontiers in Immunology, 2024)
Myasthenia gravis (MG) and idiopathic inflammatory myopathy (IIM) are autoimmune diseases of the nervous system, and their main clinical manifestation is muscle weakness. The concurrent presence of both conditions in the same patient is clinically rare and easily missed. Here, we report the case of a 74-year-old woman who went to the doctor with fluctuating weakness of the limbs and muscle pain. By analyzing the patient's history and the results of repeated frequency electrical stimulation, chest computed tomography, thigh muscle magnetic resonance imaging, serum antibody detection, lymph node biopsy, etc., she was finally diagnosed with MG-concomitant IIM with squamous cell carcinoma of the thymus. AChR antibody, Titin antibody, RyR antibody, anti-JO-1 antibody, and Ro-52 antibody tests were positive. MG-concomitant IIM is often associated with thymoma. The immunopathology mechanism may be different from that of pure MG or IIM, which needs further research.